An Evaluation Of The User Performance Impact: Health Information System Use In Kuwait Public Hospitals - Alkouse, Reem H Y A (2022)
In many developed and developing nations, health information systems (HIS) are increasing rapidly in the healthcare industry. Despite the great development in the application of information and communication technologies (ICT) in the healthcare sector, implementation complexity is increasing, posing challenges for healthcare organizations. Kuwait Government has spent significant investments in implementing HIS among healthcare facilities, and it must be ensured that the systems are maintaining their goals of meeting the users’ needs and requirements and increasing work quality and performance. Certainly, it has been noted that there aren't enough evaluation studies and research on HIS adoption in Kuwait. (Alhuwail, 2020). Therefore, this research aims to assess HIS user performance as it is important to determine the IS success by determining its influencing factors. To do so, the basic theory for this study was the DeLone and McLean Information System Success Model, integrated with Task Technology Fit theory, Trust, and User resistance. A crosssectional, self-structured questionnaire was used to collect data. According to the study, trust and TTF are positively impacted by the system, information, and service quality. Whereas trust negatively affects user resistance, which negatively affects HIS use. It was also found that information, system, and service quality positively impact TTF, which consequently affects both HIS use and user performance. Furthermore, the study proved that individual characteristics positively impact TTF, but task characteristics did not influence TTF. The research also showed that TTF and user satisfaction positively impact user performance